Anterior Cruciate Ligament Reconstruction With Bone–Patellar Tendon–Bone Autograft With Concomitant Meniscal Allograft Transplantation - Jonathan D. Groothoff MA; Richard S. Villa BS; Mark A. Glover BS; Thomas W. Mason BS; Anthony P. Fiegen MD; Jelle P. van der List MD, PhD; Brian R. Waterman MD (Video Journal of Sports Medicine)
Background: Primary arthroscopic-assisted anterior cruciate ligament (ACL) reconstruction using a bone–patellar tendon–bone (BTB) graft offers excellent long-term results for patients with ACL tears. When concurrent meniscal damage is present, the preferred treatment is repair of the meniscus. However, meniscectomy may be needed, which can result in insufficient meniscal function. Indications: ACL reconstruction performed concomitantly with meniscal allograft transplantation (MAT) is indicated for patients with ACL tears and meniscal insufficiency. This procedure is typically reserved for younger, active patients, such as the 38-year-old woman in this presentation. Technique Description: The patient was placed in the supine position. The BTB graft was harvested first using a standard medial midline incision. A posterior meniscus root tunnel was drilled, followed by drilling of the femoral tunnel for ACL reconstruction. The tibial tunnel for ACL reconstruction was subsequently created, after which tapping was performed for anterior meniscus root fixation. The meniscal allograft was secured using alternating vertical mattress inside-out sutures. Finally, the BTB graft was passed through the tibial and femoral tunnels. Results: Outcomes following ACL reconstruction with BTB autograft and MAT are positive, with a 5-year survival between 84% and 91%. ACL reinjury and long-term development of osteoarthritis are the most common complications. In this case, the patient returned to work within 7 months and reported 0 out of 10 pain. Discussion/Conclusion: ACL reconstruction with BTB autograft and concomitant MAT is a viable treatment option for patients with ACL tears in the context of meniscal deficiency. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.